2015
DOI: 10.1080/01972243.2015.998103
|View full text |Cite
|
Sign up to set email alerts
|

Another Wood Between the Worlds? Regimes of Worth and the Making of Meanings in the Work of Archivists

Abstract: The expectation that archives would function as the custodians of the longue durée of the society is paradoxical in its apparent simplicity. On the basis of an interview study of Nordic archives professionals, this article explores archives professionals experience and explicate the transformation and complexities of the worth and meaning of archival work and its major constituencies, the archival records. The analysis shows how the continuums of the worth and meaning of archival records and the work of archiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Archival practice itself, though codified in national manuals and an increasing number of international standards, is not uniform across jurisdictions, and often not even within them. 11 Huvila's study of Nordic archives professionals found that their work and the meanings of the archives they managed were strongly influenced by their individual and institutional contexts, 12 just as I found in my own earlier research into descriptive choices made by archivists in New Zealand, 13 and in line with Oliver's research into organisational culture and recordkeeping. 14…”
Section: Communities As Archival Contextmentioning
confidence: 73%
“…Archival practice itself, though codified in national manuals and an increasing number of international standards, is not uniform across jurisdictions, and often not even within them. 11 Huvila's study of Nordic archives professionals found that their work and the meanings of the archives they managed were strongly influenced by their individual and institutional contexts, 12 just as I found in my own earlier research into descriptive choices made by archivists in New Zealand, 13 and in line with Oliver's research into organisational culture and recordkeeping. 14…”
Section: Communities As Archival Contextmentioning
confidence: 73%
“…Relating to the raison d'être of archival institutions, an earlier study with Nordic archivists (Huvila, 2015a) identified five broad orders (cf. Boltanski and Thévenot, 2022) of archival work.…”
Section: The Raison D'être Of Archival Institutionsmentioning
confidence: 99%
“…The raison d'être specific subject positions show obvious kinship to the orders of work identified by Huvila (2015a). The pluralistic order of work has much in common with framing archival institutions as an arena of public discourse and learning, organizational order with the manager and provider of public information and the manager of private information, and antiquarian with the research and heritage resource.…”
Section: Participation and The Role Of Archival Institutionsmentioning
confidence: 99%
See 2 more Smart Citations